Implementasi Pembelajaran Kooperatif tipe Two Stay Two Stray (TS-ST) Sebagai Upaya Peningkatan Hasil Belajar Roll Ke Depan dalam Perkuliahan Senam - Anwar, Nur Indah Atifah (Indonesian Journal of Physical Activity, 2024)
This study aims to determine the application of the two stay two stray type coopertaif learning model in improving student roll forward learning outcomes. This research method is experimental quantitative research with randomized control group pretest-postest design. The sample in this study consisted of 79 students of gymnastics courses, consisting of experimental and control classes. The data collection technique was carried out with a forward roll skill test. The stages in this study were carried out with 3 (three) stages consisting of pre-test, treatment, and post-test. The results of the study obtained a Sig value. (2-tailed) of 0.000 and a mean value difference of 4.033. While based on the results of the N-Gain test, the mean value was 64.9%. The conclusion in this study is that the two stay two stray type coopertaif learning model is quite effective in improving student roll forward learning outcomes.